Захист інформації в клінічному інтернеті речей - Кирсанов, О. О.; Безлуцький, В. О. (ХНУРЕ, 2020)
This document illustrates a considered approach for analyzing the security considerations for components, systems and operational environments related to Clinical IoT Data and Devices. The determination of usefulness and applicability of this approach and the viability of the resulting recommendations for a specific component, device, system or operational environment is the joint responsibility of the parties who engineer the systems and devices; the parties who determine the suitability of components, devices and systems in a given operating environment